Domestic Rainwater Harvesting as a Water Supply Option in Sri Lanka - Ariyananda, Tanuja (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Domestic rainwater harvesting has been revived in Sri Lanka since 1995 with the Community Water Supply and Sanitation Project. Since then, through the efforts of the Lanka Rainwater Harvesting Forum (LRWHF, an NGO set up to pro-mote rainwater harvesting for domestic need), the technology and the concept has been spread to other parts of the country. At present there are over 31,000 domestic rainwater systems in the country. Rainwater harvesting has been successfully legalized in Sri Lanka. Key words: Rainwater harvesting; Water quality; Sri Lanka; Technology; Policy DOI: 10.3126/hn.v6i0.4189 Hydro Nepal Vol 6, January 2010 Page : 27-30 Uploaded Date: 24 January, 2011